2010
DOI: 10.1002/hep.23739
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell toll-like receptor 4 regulates fibrosis-associated angiogenesis in the liver

Abstract: Angiogenesis defines the growth of new blood vessels from preexisting vascular endothelial networks and corresponds to the wound healing process that is typified by the process of liver fibrosis. Liver fibrosis is also associated with increased endotoxin within the gut lumen and its associated portal circulation. However, the interrelationship of gut endotoxin and its receptor, toll‐like receptor 4 (TLR4), with liver fibrosis and associated angiogenesis remains incompletely defined. Here, using complementary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 50 publications
2
105
0
2
Order By: Relevance
“…Indeed, most strategies targeting angiogenic molecules have shown benefit in preclinical animal models of liver disease. 11,[31][32][33][34] In this context, our study extends the current knowledge of an emerging anti-angiogenic target, AQP1, by providing direct in vivo evidence that AQP1 regulates the angiogenesis, fibrosis, and portal hypertension that occurs after BDL; and defining a novel, molecular, fine-tuning mechanism involving osmotically sensitive miRs that may contribute to the pathological overexpression of AQP1 during cirrhosis. We previously demonstrated that AQP1 is overexpressed in the angiogenic neovasculature within fibrotic septa in human cirrhosis and in CCl 4 -induced liver injury in C57 black mice.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, most strategies targeting angiogenic molecules have shown benefit in preclinical animal models of liver disease. 11,[31][32][33][34] In this context, our study extends the current knowledge of an emerging anti-angiogenic target, AQP1, by providing direct in vivo evidence that AQP1 regulates the angiogenesis, fibrosis, and portal hypertension that occurs after BDL; and defining a novel, molecular, fine-tuning mechanism involving osmotically sensitive miRs that may contribute to the pathological overexpression of AQP1 during cirrhosis. We previously demonstrated that AQP1 is overexpressed in the angiogenic neovasculature within fibrotic septa in human cirrhosis and in CCl 4 -induced liver injury in C57 black mice.…”
Section: Discussionsupporting
confidence: 54%
“…Bacterially derived lipopolysaccharides (LPS) bind to their receptor TLR-4 expressed on SEC, inducing injury and inflammation [11]. Interestingly, recent studies have shown that LPS can also induce fibrosis-associated angiogenesis by interacting with TLR-4, highlighting the role of SEC in the so-called gut-liver axis [12,13].…”
Section: Sinusoidal Endothelial Cellsmentioning
confidence: 99%
“…Jagavelu and colleagues recently demonstrated a key role for the TLR4/MyD88 axis during VEGF production and the subsequent angiogenic process in liver endothelial cells following LPS stimulation [41]. Likewise, mycoplasma infections could be accompanied by enhanced angiogenesis and microvascular remodeling, which are features of chronic inflammation as elicited by Mycoplasma pulmonis infections of the respiratory tract [42].…”
Section: Infection and Angiogenesismentioning
confidence: 99%